Pengelolaan Pengembangan Wakaf Uang Berdasarkan Peraturan Pemerintah No. 42 Tahun 2006 Pasal 48 Pada Bank BPD DIY Syariah - Setyadi, Hendro (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Waqf money is not so familiar to the general public, this can be seen from the understanding of Indonesian society who see waqf only limited to the provision in the form of immovable goods. Nevertheless, the socialization of money waqf is not stagnant or keeps it going. This is evidenced by the existence of Law no. 41 of 2004 on Waqf and RI Government Regulation no. 42/2006 on the Implementation of Law No. 41 of 2004 on Waqf, although the implementation of waqf own money has started long after the fatwa of Majlis Ulama Indonesia (MUI) on May 11, 2002. This research is a field research with normative juridical approach in collecting Data, and using descriptive-qualitative methods in analyzing the management of money waqf development at Bank BPD DIY Syariah. Based on the research, it can be concluded that: (1). In the practice of management and development of money waqf in Bank BPD DIY Syariah, Bank BPD DIY Syariah acts as nadzir in fund raising and as a fund institution of waqf fund and for the distribution of bank BPD DIY Syariah in cooperation with Badan Wakaf Uang / Tunai (BWUT) . (2). The management and development of the money wakaf of Bank BPD DIY Syariah has been in accordance with the provisions of Article 48 of Government Regulation no. 42 of 2006 Keywords: Waqf, Waqf Money, Islamic Financial Institutions